Consumers’ purchase intention towards edible bird’s nest based products - Awang, Siti Nur Soleha (2018)
Edible bird’s nest (EBN) has been known very nutritious and can cure several of diseases. It is the expensive animal products that have been consume by human. Tradionally, EBN was consumed as raw and served as a soup. But now, there were already has been processed into a form of products such as in form of drinking, cosmetics products and supplements. A lot of people aware about its benefit but their awareness does not mean that they have an intention to purchase on it. Hence, this study aimed to study the consumers’ purchase intention towards edible birds’ nest (EBN) based products among Malaysian consumers. The specific objective is to identify the association between socio-demographic profile and consumers’ purchasing intention towards Edible Bird Nest (EBN) based products and to determine the factors that influencing consumers purchase intentions towards EBN-based products. These factors included attitude towards intention to purchase edible bird’s nest based products, subjective norms, perceived behavioral control, as well as demographic characteristics such as gender, income, race, marital status, occupation and religion. 400 respondents were selected around Klang Valley area to complete the questionnaire. Findings concluded that attitude, subjective norm and perceived behavior were the factors that influencing consumers to have intention in purchasing EBN based products. Among these variables, attitude was the strongest predictor. Besides that, demographic characteristic such as race and income was found significant in purchase intention of EBN based products. In fact, majority of respondents have intention in purchasing edible bird nest. These findings also can help the entrepreneur to understand that race and income become the main things that can influence consumers’ purchase intention towards EBN based products.